Preoperative inflammatory scores do not accurately predict early recurrence of pancreatic ductal adenocarcinoma after resection: a systematic review and meta-analysis - Castro e Borges, Filipe de; Khajeh, Elias; Nikbakhsh, Rajan; Ribeiro, Catarina; Maeurer, Markus; Carvalho, Carlos; Gonçalves, Gil; Berchtold, Christoph; Büchler, Markus W.; Mehrabi, Arianeb (Cancer medicine, 2024)
Background Disease recurrence after surgical resection for pancreatic ductal adenocarcinoma can affect more than 50% of patients in the first 12 months after resection. The goal of this current systematic review and meta-analysis is to assess the ability of preoperative inflammatory scores to predict early recurrence after resection and to identify the best candidates for surgical resection. Methods Medline and Web of Science databases were searched for studies reporting inflammatory scores and oncological outcomes in patients with PDAC after curative-intent resection. The systematic review revealed that the most common scores were modified Glasgow Prognostic Score (mGPS), Prognostic Nutritional Index (PNI), platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and Systemic Immune-Inflammation Index (SII). After, a meta-analysis was performed to determine the prognostic value of these scores in early recurrence (12 months) after resection. A subgroup analysis was also carried out in patients who had upfront surgery and in those who underwent neoadjuvant chemotherapy. The ROBINS-I tool was used to assess the risk of bias. Results The literature search retrieved 1864 articles, 16 of which were eligible for analysis. The included studies comprised 4460 patients. Nine studies reported outcomes for mGPS, four studies for PNI, seven studies for PLR, eight studies for NLR, and two studies for SII. In the meta-analysis, mGPS, NLR, and PLR showed significantly higher rates of early recurrence in the high-score groups compared to the low-score groups. Analyzing the sensitivity and specificity of these scores showed no significant difference in their diagnostic accuracy (mGPS area under the curve [AUC] = 0.534; NLR AUC = 0.628, and PLR AUC = 0.607). High and low PNI and SII scores demonstrated similar rates of early recurrence. Conclusion mGPS, PNI, PLR, NLR, and SII scores did not show a suitable diagnostic accuracy to predict PDAC recurrence in the first 12 months after resection. Therefore, these inflammatory scores should not be used to select the best candidates or to preclude a possible surgical indication.